ECHOVIRUS TYPE 30 MENINGITIS AND RELATED FEBRILE ILLNESS: EPIDEMIOLOGIC STUDY OF AN OUTBREAK IN AN ESKIMO COMMUNITY - KAPLAN, GARY J.; CLARK, PAUL S.; BENDER, THOMAS R.; FELTZ, ELMER T.; LIST-YOUNG, BETTY; NEVIUS, S. EDWARD; CHIN, T. D. Y. (Oxford University Press, 1970)
Kaplan, G. J. (Arctic Health Research Center, Anchorage, Alaska 99501), P. S. Clark, T. R. Bender, E. T. Feltz, B. List-Young, S. E. Nevius and T. D. Y. Chin. Echovirus type 30 meningitis and related febrile illness: Epidemiologic study of an outbreak in an Eskimo community. Amer. J. Epid ., 1970, 92: 257–265.—An outbreak of echovirus 30 aseptic meningitis and related febrile illness involving 160 persons occurred in Kotzebue, Alaska, during the fall of 1969. Virus isolation and/or fourfold rises in antibody titer were obtained in 36 cases. The illness was characterized by fever, headache, nausea, and vomiting. Stiff neck, photophobia, weakness and lethargy were also common but rash was present in only two cases. A random family survey of 60 households comprised of 344 people revealed an overall attack rate of 27%, with the highest age specific attack rate in the 5- to 14-year age group. The virus demonstrated a high affinity for Wistar 38 strain of human embryonic fibroblast cells.